Mosaic vaccine-induced antibody-dependent cellular phagocytosis associated with delayed HIV-1 viral load rebound post treatment interruption - Thembi Mdluli; Bonnie M. Slike; Daniel J. Curtis; Zhanna Shubin; Ursula Tran; Yifan Li; Vincent Dussupt; Letzibeth Mendez-Rivera; Suteeraporn Pinyakorn; Daniel J. Stieh; Frank L. Tomaka; Hanneke Schuitemaker; et al. (Cell Reports, 2024)
Summary: A heterologous Ad26/MVA vaccine was given prior to an analytic treatment interruption (ATI) in people living with HIV-1 (mainly CRF01_AE) who initiated antiretroviral treatment (ART) during acute HIV-1. We investigate the impact of Ad26/MVA vaccination on antibody (Ab)-mediated immune responses and their effect on time to viral rebound. The vaccine mainly triggers vaccine-matched binding Abs while, upon viral rebound post ATI, infection-specific CRF01_AE binding Abs increase in all participants. Binding Abs are not associated with time to viral rebound. The Ad26/MVA mosaic vaccine profile consists of correlated non-CRF01_AE binding Ab and Fc effector features, with strong Ab-dependent cellular phagocytosis (ADCP) responses. CRF01_AE-specific ADCP responses (measured either prior to or post ATI) are significantly higher in individuals with delayed viral rebound. Our results suggest that vaccines eliciting cross-reactive responses with circulating viruses in a target population could be beneficial and that ADCP responses may play a role in viral control post treatment interruption.